Alterações histológicas no sistema digestório de ovinos submetidos à dieta a base de feno da parte aérea da mandioca e palma forrageira - Barboza, Samara da Costa Ribeiro (2018)
The aim of this study was to identify and to evaluate the histological alterations in digestive system of sheeps submitted to the diet containing cassafa hay. Thirty five lambs non defined breed, intact males, weighing 16 kg, were evaluated. The treatments were constituted by five diets: 1- massive fraction of Tifton hay; 2- total replacement of Tifton by cassava hay (CH); 3- 5-35% of Tifton hay and 35% of CH; 4- 35% of Tifton and 35% of palm and 5- 35% CH and 35% palm, based on dry matter. Histological and histomorphometric analyzes were performed on liver, kidney, rumen and small intestine. The use of alternative foods did not affect the performance of the animals, thus having a better performance for the conversion and food efficiency, average daily gain and dry matter intake. The diet with CH + palm had a positive effect on papilla height. Papilla width decreased with the CH + palm and Tifton + palm diets. The absorption area did not differ between the diets. The muscular layer thickness was higher in the diet containing 35% of Tifton hay and 35% of CH as well as in the diet containing 35% of CH and 35% of palm. The keratin layer was higher in the diet containing 35% of CH and 35% of palm. The diets did not affect the intestinal morphometry and villi. The crypts were deeper in the diets with palm and the relation villi/crypt was the same to all diets. Goblet cells decreased with the diet CH or palm. Congestion, vacuolization and proteins were observed in the diet containing 35% of Tifton hay and 35% of CH. The cassava hay may be used as an alternative food to sheeps.